Optogenetic regulation of phosphatidylinositides in cellular and mouse models of Alzheimer's disease. (20th December 2022) - Costa, Ana Paula; Acquarone, Erica; Lazarian, Artur; Herman, Mathieu A; Arancio, Ottavio; Hussaini, S Abid; McIntire, Laura Beth
Abstract: Background: Major disappointments in late‐stage clinical trials have made it clear that additional therapeutic targets beyond amyloid β‐peptide (Aβ) and tau are urgently required for Alzheimer's disease (AD). Phosphatidylinositol 4, 5‐biphosphate [PI(4, 5)P2 ] has previously been established as an important signaling lipid at the synapse and in a mouse model of Alzheimer's disease. We hypothesize that the level of PI(4, 5)P2 in the plasma membrane may be an early and critical determinant of AD associated molecular and behavioral deficits in cellular and mouse models of the disease. Method: We tested the ability of a light‐inducible dimerization system to modify phosphoinositide content in vitro using a PC12 cell line overexpressing cryptochrome‐interacting basic‐helix‐loop‐helix (CIBN) fusion to a membrane targeted CAAX domain (CIBN‐CAAX), and blue‐light mediated binding of cryptochrome 2 (CRY2) fused with the catalytic domain of phosphatidylinositol 4‐phosphate 5‐kinase (CRY2‐PIP5K2A‐CD). We detected PI(4, 5)P2 using the PI(4, 5)P2 sensor plextrin homology domain of phospholipase C δ (PH‐PLCδ). Using virally mediated transduction of these constructs in mouse brain, we manipulated PI(4, 5)P2 levels in hippocampus of a mouse model of AD, harboring the Amyloid Precursor Protein transgene (APP‐Tg). Behavioral deficits were assessed using novel object recognition (NOR). Brains were analyzed for detection of phosphoinositide using Imaging Mass Spectrometry. Result: In PC12 cells, initial results indicate that after optogenetic stimulation, cytosolic labeling by PH‐PLCδ was largely lost, and plasma membrane labeling was observed. In a mouse model of AD (APP‐Tg) after stimulation with blue light or control yellow light, behavioral paradigms including NOR were completed. NOR discrimination index was significantly reduced for Tg+/control compared to other groups (WT/control, WT/Opto) as expected. However, Tg+/Opto was not significantly different than WT/control or WT/Opto indicating amelioration of behavioral deficits in Tg+/Opto through optogenetic stimulation of PI(4, 5)P2 production. Experimental groups did not show significant changes in motor function in the open field task. Our data indicate that optogenetic stimulation of PI(4, 5)P2 accumulation in brain is able to rescue behavioral AD associated behavioral deficits. Conclusion: Using sophisticated and specific optogenetic manipulation we have demonstrated that stimulation of PI(4, 5)P2 synthesis rescued behavioral deficits in a mouse model supporting the critical role of PI(4, 5)P2 levels in AD.